Problem analysis of health tourism sector - Kozmáné Csirmaz, Éva (Acta Agraria Debreceniensis, 2013)
On the basis of experts health tourism is one of the most dynamically developing sectors within tourism. The outstanding role of the sector is partly owing to increasing health consciousness and partly to aging society – beside numerous other factors. But health tourism in Hungary is hit by several problems in spite of the fact that recently particular attention is paid to this sector. It can be mentioned as a difficulty that supply of education system is not in conformity with market demands, thus fresh supply of experts is not appropriate. As a world trend, classic position of thermal baths based on natural curative factors is getting to be displaced by adventure baths, which is unfavourable for health tourism. Notwithstanding that Hungary is in a distinguished place on a world scale as regards tourist arrivals, yet we are only in a mid-filed position relating to industrial revenues. Suppliers of this sector do not pay enough attention to disabled persons. The established TDM Organisations have to cope with numerous challenges. Nevertheless experts agree that high support of health tourism can be suggested despite to problems, market risks and significant international competition. However, this support has to be more aimed than before and has to be rather founded on world trends.